Vapor Permeability of Thin-Film Composite Materials Based |on Polyethylene - Domantsevich, N.; Yatsyshyn, B. (Physics and Chemistry of Solid State, 2019)
The study of the vapor permeability and surface structure of polyethylene films modified with organic filler (casein) and mixed organic-mineral fillers stored under closed storage conditions have been shown. Changes in diffusion characteristics are shown depending on the type and amount of filler in long-term (up to 7 years) studies. It was established that the injection into the polyethylene matrix of fillers and additives significantly changes the structure formation with long-term aging. Water vapor permeability of polyethylene film modified by fillers increases along the subsequent aging. However, the deviation of characteristics at 7 years of storage does not exceed the value of WVTR = 0.6 mg·m-2·s-1, even taking into account the small thickness of the samples, which in most cases the long-term use of such a product is permissible. Electron microscopic studies of modified films have been carried out.